Labour Market and EU Enlargement: Is there a Real Threat for EU – 15? - Florin Bonciu (Romanian Journal of European Affairs)
The paper analyzes the existing and potential impact of 2004 and 2007 enlargements on EU economy and argues that in order to increase its competitivity on the global market EU needs to deepen the liberalization of markets. More focus is put on the implications of the liberalization of the labor market and answers are found to the fears expressed in Western Europe on the effects of enlargements on local labor markets, particularly vis-à-vis the forthcoming accession of Romania and Bulgaria in January 2007.